2010
DOI: 10.1111/j.1601-6343.2010.01495.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between genotype and supernumerary tooth formation in cleidocranial dysplasia

Abstract: Individuals with identical gene mutations showed a wide variation in the supernumerary tooth formation. Not only the genotype but also environmental factors and a complex system including epigenetics and copy number variation might regulate supernumerary tooth formation in CCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 18 publications
1
41
0
Order By: Relevance
“…Furthermore, in eight out of nine cases, MZ co-twins were discordant for the number of supernumerary teeth [62]. A recent study of nine Japanese individuals with cleidocranial dysplasia showed considerable variation in expression of supernumerary teeth in individuals with the same gene mutations, as well as discordance in a pair of monozygotic twins [63]. These findings support the view that supernumerary tooth formation is influenced not only by genetic factors but also by environmental and epigenetic influences (Fig.…”
Section: New Methods Of Shape Analysismentioning
confidence: 58%
“…Furthermore, in eight out of nine cases, MZ co-twins were discordant for the number of supernumerary teeth [62]. A recent study of nine Japanese individuals with cleidocranial dysplasia showed considerable variation in expression of supernumerary teeth in individuals with the same gene mutations, as well as discordance in a pair of monozygotic twins [63]. These findings support the view that supernumerary tooth formation is influenced not only by genetic factors but also by environmental and epigenetic influences (Fig.…”
Section: New Methods Of Shape Analysismentioning
confidence: 58%
“…Intra-oral examination reveal several features, with the most being, hypoplastic teeth, retained primary teeth, delayed eruption of permanent teeth, mesial step molar relationship and CL I canine relationship, which were previously reported in several studies [10][11][12]. Moreover, multiple caries was observed in this case which might be attributed to the poor oral hygiene and diet habit of this patient.…”
Section: Discussionmentioning
confidence: 57%
“…However, in this family no evidence was reported of a coexisting missing tooth. The molecular pathogenesis of CCD is related to the loss of function or haploinsufficiency of RUNX2,7 an osteoblastic-specific transcription factor belonging to the Runt domain gene family that promotes the differentiation of mesenchymal cells into osteoblasts 8. Mutations in the RUNX2 gene in humans cause CCD,9 and the patients present bone dysplasia and extra teeth 2.…”
Section: Discussionmentioning
confidence: 99%